Penerapan Komunikasi Terapeutik Melalui Pendidikan Kesehatan tentang Lifestyle pada Penderita Hipertensi - Sudarsih, Sri; Santoso, Windu; Taqiuddin, Muhammad Hafidh; Fadhilah, Khoirunnisa Nurul (Universitas Methodist Indonesia, 2024)
Hypertension sufferers need to be fully aware of the importance of lifestyle modification in controlling high blood pressure as well as the need for comprehensive health education and health promotion programs for hypertension sufferers. This community service activity aims to apply therapeutic communication through health education about lifestyle for hypertension sufferers. Community service activities were carried out by the team on July 22 2023 regarding the implementation of therapeutic communication through lifestyle education for hypertension sufferers at Posbindu in the Kedungsari area, Mojokerto City. This community service activity is in collaboration with cadres and people in charge of the Kedundung Community Health Center, Mojokerto City. Most of the participants' knowledge increased in the good category, 16 participants (67%) and the sufficient category, 33 participants (33%). This community service activity is an implementation of therapeutic communication through education that goes according to plan and the evaluation results show an increase in participants' knowledge after being provided with education. Educational activities implementing therapeutic communication need to be continued and programmed for students as an effort to improve their ability to apply therapeutic communication.